Diagnostic Accuracy of the Optical Coherence Tomography in Assessing Glaucoma Among Filipinos. Part 2: Optic Nerve Head and Retinal Nerve Fiber Layer Parameters - Noel de Jesus Atienza, MD, MSc; Joseph Anthony Tumbocon, MD (Philippine Journal of Ophthalmology)
Objective: To determine the accuracy of the optic nerve head (ONH) and retinal nerve fiber layer (RNFL) parameters using the Stratus OCT in the diagnosis of glaucoma and to determine the validity of these measurements.